Effects of half ironman competition on the development of late potentials - Warburton, D. E.; Welsh, R. C.; Haykowsky, M. J.; Taylor, D. A.; Humen, D. P.; Dzavik, V. (Medicine & Science in Sports & Exercise, 2000)
Objectives: The primary purpose was to evaluate the prevalence of late potentials (LPs) in triathletes before and after a half ironman triathlon. The secondary purpose was to examine whether LPs are the electrocardiographic expression of a greater myocardial mass. Methods: Nine asymptomatic male triathletes (mean age ± SD, 32 ± 5 yr) were examined using signal-averaged ECG (SAECG) 48-72 h before (PRE), immediately after (POST), and 24-48 h after the completion (RECOVERY) of a half ironman triathlon. Late potentials were considered to be present if two of the following SAECG anomalies were observed: 1) a prolonged filtered QRS (fQRS) complex (>114 ms), 2) a lengthened low amplitude signal (LAS) duration (>38 ms), and/or 3) a low root mean square (RMS) voltage of the last 40 ms of the fQRS (<20 µV). Left ventricular dimensions were determined at PRE using M-mode echocardiography. Results: There were no significant differences between PRE, POST, and RECOVERY in the fQRS duration, the LAS duration, or the RMS voltage. Two athletes displayed a single SAECG abnormality during PRE and two SAECG anomalies (i.e., LPs) during POST. Late potentials remained in one of the two athletes during RECOVERY. A moderate relationship existed between fQRS and left ventricular mass (r = 0.67, P < 0.05). Conclusions: Ultra-endurance training and/or events do not lead to LPs in the majority of triathletes who do not possess ventricular arrhythmias. However, a small subset of triathletes do display SAECG anomalies, which are augmented by an ultra-endurance event and may persist even after recovery from the event. Left ventricular mass does not affect overall SAECG parameters.